(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation: This annotation offers an eye-opening look at how inductive grammar instruction can change the way we understand and experience English. It's about taking our language skills to the next level, unlocking the deeper layers of English proficiency that truly capture the essence of language fluency and adaptability.